Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1155/2020/5108298
|View full text |Cite
|
Sign up to set email alerts
|

Aloe‐Emodin Induces Breast Tumor Cell Apoptosis through Upregulation of miR‐15a/miR‐16‐1 That Suppresses BCL2

Abstract: Purpose. Aloe-emodin (AE) is a natural compound derived from aloe vera and palmatum rhubarb and shows anticancer activities in various cancers. Bcl-2 family is the main regulator of cell death or cell survival. This study describes the effects of AE on proliferation of breast tumor (BT) cells. Methods. MCF-10A, MCF-10AT, MCF-7, and MDA-MB-231 cell lines were exposed to AE. Cell proliferation and apoptosis were assessed by CCK-8 and flow cytometry. Protein levels were measured by Western blotting. The levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 32 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Aloe-emodin was reported to specifically inhibit MCF-10AT and MCF-7 cell growth, but did not exert any toxicity against the human non-tumorigenic spontaneously immortalised breast epithelial cell line MCF-10A (52). Furthermore, administration of aloe-emodin did not result in any cytotoxicity towards human peripheral mononuclear cells at all concentrations tested in the 0.001-100 µM range, whilst the IC 50 values of aloe-emodin towards the lymphoblastic leukaemia cell line CCRF-CEM, the human colorectal carcinoma cell line HCT116, U87MG, the human breast adenocarcinoma MDA-MB-231 cell line and the tumorigenic human cell line 293T were in the 9.8-22.3 µM range (102).…”
Section: Anticancer Selectivitymentioning
confidence: 99%
“…Aloe-emodin was reported to specifically inhibit MCF-10AT and MCF-7 cell growth, but did not exert any toxicity against the human non-tumorigenic spontaneously immortalised breast epithelial cell line MCF-10A (52). Furthermore, administration of aloe-emodin did not result in any cytotoxicity towards human peripheral mononuclear cells at all concentrations tested in the 0.001-100 µM range, whilst the IC 50 values of aloe-emodin towards the lymphoblastic leukaemia cell line CCRF-CEM, the human colorectal carcinoma cell line HCT116, U87MG, the human breast adenocarcinoma MDA-MB-231 cell line and the tumorigenic human cell line 293T were in the 9.8-22.3 µM range (102).…”
Section: Anticancer Selectivitymentioning
confidence: 99%
“… 15 , 16 Aloe emodin can induce apoptosis of MCF-10AT and MCF-7 cells by up-regulating miR-15a/miR-16-1 of Bcl-2. 33 Acetyl-11-keto-β-boswellic acid can inhibit the expression of ER-α protein through LINC00707/miR-206, thus promoting the apoptosis of MCF-10AT cells and inducing the cell cycle arrest of GO/G1 phase. Boswellic acid can be used as an effective anticancer drug, affecting angiogenesis (VEGF), inflammation (TNF-α, IL-12), apoptosis (caspase-3, caspase-9) and antioxidants (SOD and CAT), thus inhibiting the proliferation of MCF-7 cells and enhancing VEGF antibody induced cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Rhein was reported to protect liver cells from methotrexate-induced injury through modulating apoptosis-related proteins, such as caspase-3 and Bcl-2 family [ 22 ]. On the contrary, some studies reported that all the above compounds could induce apoptosis in many cancer models with different doses [ 23 25 ]. Therefore, future studies should explore the differences in drug targets and involve discussion about the relationship between dose and bidirectional effect.…”
Section: Discussionmentioning
confidence: 99%